Reinterpreting Online Gambling in Divorce Cases (Analysis Based on the Concept of al-Sabab in Uṣūl al-Fiqh) - Sabil, Jabbar; Rizal, Yuni Amalia (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
This study examines the phenomenon of the high rate of divorce lawsuits filed by wives in Aceh, particularly within the jurisdiction of the Mahkamah Syar’iyah Banda Aceh, which is significantly associated with online gambling behavior. The main issue in this research is the tendency of judges to inaccurately construct online gambling as a cause for divorce, where they often equate it with physical causality or deterministic natural laws. So the author conducted research with the following problem formulation: 1) How do judges consider online gambling as a cause for divorce in the Mahkamah Syariyah Banda Aceh, and 2) How is online gambling considered a cause for divorce based on the concept of al-sabab in the science of uṣūl al-fiqh. The data collected in this research is textual, so it must be analyzed using content analysis. The content analysis method is a technical step of text inference to ensure the text aligns with the context. This study found that the basis of judges' decisions and actions is not physical causality, but logical implications, known as philosophical causality. The two differ because physical causality is deterministic, while philosophical causality is probabilistic. Since judges cannot make their own laws, the causality held in legal discovery is the cause and effect desired by the Law Maker. Meanwhile, Islamic Family Law stipulates that disharmony is the cause of divorce, so disharmony is the true cause of divorce, while online gambling is a prerequisite for that true cause. In the science of Islamic jurisprudence (uṣūl al-fiqh), this is called sharṭ al-illah. An in-depth understanding of the concept of al-sabab is highly recommended for judges to ensure that their legal arguments align with Islamic legal theory, as well as to maintain public trust in the judicial institution.